Gerakan IMASI (Gerakan Imunisasi dan ASI Eksklusif) - Januarti, Luluk; Abdillah, Alvin; Nur Komari, Selvia; Firdaus, Naylufar (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2026)
Background: Low immunization coverage and exclusive breastfeeding coverage are problems in various regions. This program is caused by a lack of maternal knowledge and family support. This problem increases the risk of infection, growth disorders, and impacts the health status of infants. Therefore, the IMASI MOVEMENT (Immunization and Exclusive Breastfeeding Movement) is needed to increase community knowledge and participation regarding infant and toddler health. Method: The methods used include interactive counseling, demonstrations of breastfeeding techniques according to the pink book (KIA), distribution of leaflets, and evaluation through pre-tests and post-tests. Evaluation was carried out on aspects of structure, process, results, and impact of the activity. Results: The results of the activity showed an increase in participants' knowledge scores by ?50–60% after education. Participant attendance reached ?85% of the target, and there was an increase in participation in integrated health post activities compared to the previous month. Discussion: The increase in knowledge scores in the post-test results compared to the pre-test indicates that the educational intervention is effective in increasing mothers' understanding of the benefits of exclusive breastfeeding and the importance of immunization. These findings indicate that community-based health education is an effective strategy to improve maternal health literacy and has the potential to increase the coverage of exclusive breastfeeding and complete basic immunization. Conclusion: This program has proven effective in increasing awareness and health behavior of mothers and toddlers as an effort to prevent stunting and infectious diseases.